Still ain’t no black in the Union Jack? – afro-brytyjskość w twórczości czarnych autorów z Wielkiej Brytanii na przykładzie Dottie Abdulrazaka Gurnaha .......... 233 - Binczycka-Gacek, Elżbieta (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
STILL AIN’T NO BLACK IN THE UNION JACK? – AFRO-BRITISHNESS IN THE WORK OF BLACK UK AUTHORS: THE CASE OF DOTTIE BY ABDULRAZAK GURNAH The aim of the article is to examine the construction and problematization of Afro-British identity in the literature of non-white authors from the United Kingdom, with a focus on Abdulrazak Gurnah’s novel Dottie. The author reconstructs the debates surrounding the concept of “Black British literature,” emphasizing its complexity and ambiguity. Through intertextual references to the British literary canon (particularly Charles Dickens’s David Copperfield) Gurnah exposes the limitations of the cultural inclusivity of “Englishness” and offers a critical reflection on its character. The article argues that, in Gurnah’s work, Black Britishness is an identity process situated between memory and marginalization, and that literature can serve as a tool of resistance against exclusionary national narratives.